2003
DOI: 10.1038/ng1236
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and biomedical implications of a Schistosoma japonicum complementary DNA resource

Abstract: Schistosoma japonicum causes schistosomiasis in humans and livestock in the Asia-Pacific region. Knowledge of the genome of this parasite should improve understanding of schistosome-host interactions, biomedical aspects of schistosomiasis and invertebrate evolution. We assigned 43,707 expressed sequence tags (ESTs) derived from adult S. japonicum and their eggs to 13,131 gene clusters. Of these, 35% shared no similarity with known genes and 75% had not been reported previously in schistosomes. Notably, S. japo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
202
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(211 citation statements)
references
References 46 publications
6
202
1
2
Order By: Relevance
“…The recent appearance in GenBank of . 40,000 cDNAs, which may include the complete transcriptome of the adult stage of S. japonicum (Hu et al, 2003), enabled us to re-interrogate the public databases with accession nos. U83906 and AF300423.…”
Section: Classification Of the Schistosome Aminopeptidase Based On Prmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent appearance in GenBank of . 40,000 cDNAs, which may include the complete transcriptome of the adult stage of S. japonicum (Hu et al, 2003), enabled us to re-interrogate the public databases with accession nos. U83906 and AF300423.…”
Section: Classification Of the Schistosome Aminopeptidase Based On Prmentioning
confidence: 99%
“…However, by analysing the more recent S. japonicum sequence entries (Hu et al, 2003), we completed the 5 0 end of the LAP gene of this species and identified the start methionine. The protein sequence of the S. japonicum LAP (AF300423) was missing 26 NH 2 -terminal amino acids (see accession no.…”
Section: Functional Expression Of Recombinant S Mansoni Lap In Insecmentioning
confidence: 99%
“…The use of such strategies permitted the intensive sequencing of schistosomes' genome and transcriptome over the past few years and has greatly influenced the approaches employed to understand parasite biology. Two large-scale, independent, sequencing projects on S. mansoni and japonicum transcriptomes [23,24] allowed, for the first time, a broad sampling of components from the parasites' molecular systems. Analysis of the gene collection represented by the ESTs is based on the inferred functions, which are deduced from alignments of the predicted protein products with proteins of known function from other organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, before large-scale sequencing of the parasites' transcriptomes a considerable number of spectra generated by mass spectrometry of schistosome peptides could not be reliably associated with an orthologous protein from public databases. In that scenario, generation of large databases of schistosome coding sequences [23,24] has greatly improved the level of identification in proteomic studies of these organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Initialement focalisé sur le transcriptome, via le séquençage d'Expressed sequence tags [3,4], le projet s'est ensuite orienté vers la cartographie et le séquençage génomique, grâce à la construction de banques de grands fragments dans des Bacterial artificial chromosomes (BAC) [5]. Toutefois, le séquençage complet de certains de ces BAC, ainsi que le séquençage étendu de leurs extrémités, ont démontré l'impossibilité d'effectuer une « marche sur le génome » à cause de la présence massive de séquences répétées.…”
unclassified